FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEPUASAN PENGGUNA APLIKASI PELAPORAN KEUANGAN PEMERINTAH - Amin Nursudi; Sudarno Sudarno (Diponegoro Journal of Accounting, 2013)
This study aims to examine the factors that influence user satisfaction of government financial reporting application. The government financial reporting application is one of the Accounting Information Systems (AIS) operational device that applied in the central government agency. Given the important role of this application, both in the obligation implementation of the preparation and submission of financial statements currently or in the process of further development for the Treasury State Budget System (SPAN) implementation, it is necessary to measure the user satisfaction of the government financial reporting application as a form of evaluation of the AIS implementation success. The data obtained using questionnaires that distributed to all accounting units in the regional payment of Padang Treasury Office (KPPN). Furthermore, the data used to test all variables in the study with multiple regression analysis. The data were processed with SPSS version 16.0. The study results showed that the factors used in this study model can explain the variability of the user satisfaction by 83%. The study results showed that the application quality, information quality, human resources and Treasury Office (KPPN) services had positive effect on user satisfaction. On the other hand, the study results also showed that the management support had positive effect but not significant on user satisfaction.